2018
DOI: 10.1016/j.jhazmat.2018.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Oral bioaccessibility of semi-volatile organic compounds (SVOCs) in settled dust: A review of measurement methods, data and influencing factors

Abstract: Many semi-volatile organic compounds (SVOCs), suspected of reprotoxic, neurotoxic or carcinogenic effects, were measured in indoor settled dust. Dust ingestion is a non-negligible pathway of exposure to some of these SVOCs, and an accurate knowledge of the real exposure is necessary for a better evaluation of health risks. To this end, the bioaccessibility of SVOCs in dust needs to be considered. In the present work, bioaccessibility measurement methods, SVOCs' oral bioaccessibility data and influencing factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 88 publications
0
22
1
Order By: Relevance
“…Liu et al found that higher bioaccessibility of PAHs in large particle-size indoor dust (200-2000 µm) than in smaller particles (Liu et al 2018). Some studies observed oral bioaccessibility increases with decreasing particle size, and attributed this to the higher speci c surface areas of small particles (Raffy et al 2018;Wang et al 2013b). To our knowledge, there is only one study to date describing the effect of particle-size of airborne particles, which found a generally increasing trend of bioaccessibility of trace elementals with decreasing particle size (Niu et al 2010).…”
Section: Oral Bioaccessibility and In Uencing Factorsmentioning
confidence: 99%
“…Liu et al found that higher bioaccessibility of PAHs in large particle-size indoor dust (200-2000 µm) than in smaller particles (Liu et al 2018). Some studies observed oral bioaccessibility increases with decreasing particle size, and attributed this to the higher speci c surface areas of small particles (Raffy et al 2018;Wang et al 2013b). To our knowledge, there is only one study to date describing the effect of particle-size of airborne particles, which found a generally increasing trend of bioaccessibility of trace elementals with decreasing particle size (Niu et al 2010).…”
Section: Oral Bioaccessibility and In Uencing Factorsmentioning
confidence: 99%
“…This great difference could be resulted in an overestimation of cancer risks when considering total concentrations instead of using bioaccessible/bioavailable concentrations. Within this context, many authors have already reported the necessity to consider bioaccessibilities and bioavailabilities on exposure and health risk models, providing a more realistic assessment (Huang et al 2014b(Huang et al , 2018Kastury et al 2018;Raffy et al 2018;Gao et al 2018;Moreda-Piñeiro et al 2019). In addition, it is important to point out that our health risk assessment could be overestimated even using oral bioavailable concentrations because of not considering other parameters such as PM 10 deposition in different lung regions and clearance rates.…”
Section: Human Health Risk Assessment Of Pm10-bound Pahsmentioning
confidence: 99%
“…However, in vitro oral bioaccessibility studies of organic pollutants in particulate matter were not found in the literature, while there were some studies applied to indoor/outdoor dust and soils for organic compounds, i.e. PAHs (Tang et al 2006;Kang et al 2011;Collins et al 2013;Li et al 2015;Kademoglou et al 2018a), organophosphate flame retardants (Quintana et al 2017), semi-volatile organic compounds (Raffy et al 2018), polychlorinated biphenyls (Wang et al 2013) and polybrominated diphenyl ethers (Yu et al 2011;Kademoglou et al 2018b;Gao et al 2019b). The stringent analytical requirements (target pollutants enrichment, due to the low levels; and pollutant isolation from the synthetic fluids matrix) for organic pollutant quantification in bioaccessible/bioavailable fractions might explain the scare information.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the contamination of dust by SVOCs may occur via volatilization and recondensation of the SVOCs on dust particles, direct transfer from horizontal surfaces to dust, or weathering or abrasion of polymers [58]. SVOCs can therefore be sorbed onto the surface of dust particles or be a constituent of these particles, which may explain why some compounds presented higher RSDs than others for the same sample.…”
Section: Application To Five Real Dust Samplesmentioning
confidence: 99%